1994
DOI: 10.1096/fasebj.8.12.8088461
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular processing of lung surfactant 1

Abstract: Pulmonary surfactant, a complex material that lines the alveolar surface of the lung, is synthesized in the type II pneumocyte. Surfactant consists largely of phospholipids, of which phosphatidylcholine is by far the most abundant component, and is mainly responsible for surface activity. Surfactant also contains four unique proteins, surfactant protein (SP)-A, SP-B, SP-C, and SP-D, which are synthesized in a lung-specific manner. SP-A and SP-D are glycoproteins (M(r) approximately 30,000-40,000) whereas SP-B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
205
1
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(212 citation statements)
references
References 88 publications
5
205
1
1
Order By: Relevance
“…The PLD pathway has been implicated in a number of physiological functions, including secretion. For example, as elaborated in LPPs and lung function, surfactant secretion can be controlled in this manner (209,212).…”
Section: Substrates For Lppmentioning
confidence: 99%
See 2 more Smart Citations
“…The PLD pathway has been implicated in a number of physiological functions, including secretion. For example, as elaborated in LPPs and lung function, surfactant secretion can be controlled in this manner (209,212).…”
Section: Substrates For Lppmentioning
confidence: 99%
“…Surfactant secretion can be stimulated in isolated alveolar type II cells through three distinct signal transduction pathways: 1) A 2␤ -adenosine or ␤ 2 -adrenergic receptors influencing activation of adenyl cyclase; 2) stretch and other receptors leading to influx of Ca 2ϩ and activation of calcium-calmodulin effectors; and 3) P2Y2 purinergic receptors resulting in PI-PLC activation, DAG activation of PKC, and elevation of intracellular Ca 2ϩ by IP 3 . Considerable cross talk occurs between these systems (152,209,210,212).…”
Section: Pap1mentioning
confidence: 99%
See 1 more Smart Citation
“…For further details, several reviews and books covering the processing (Beers and Fisher, 1992;Rooney et al, 1994), regulation (Weaver and Whitsett, 1991), host-defense properties (Robertson et al, 1992;Pison et al, 1994), proteins Joliansson et al, 1994a;Vandenbussche et al, 1995;Whitsett et al, 1995) and clinical aspects (Robertson and Taeusch, 1995) of pulmonary surfactant are available.…”
mentioning
confidence: 99%
“…Pulmonary surfactant plays an essential role in reducing the surface tension of the air-liquid interface of the alveoli, thereby preventing alveolar collapse (atelectasis) during expiration (16). A growing body of evidence has suggested that pulmonary surfactant is correlated with the development of COPD.…”
mentioning
confidence: 99%